The Air Polution and Noise Of diesel Energy Source (Cases Study In PLTD Kota Bitung Sulawesi Utara) - B. Limbong Tampang (Indonesian Chemistry Letter, 2002)
The aims of this are to find out: 1) The air pollution level a result of the diesel energy source activity. 2) the noise level as a result of the diesel energy source activity. The research was conducted in PLTD Kota Bitung Propinsi Sulawesi Utara. The data was colected from February to June 1999.